A linear binomial is a factor of a polynomial if the polynomial value is 0 at the zeros of the linear binomial
Assume a polynomial function is
P(x) = (x - 3)(x + 1)(x -2)
And a linear binomial is:
x - 3 = 0
We start by calculating the value of x in x - 3 = 0
x = 3
Next, we substitute x = 3 in P(x) = (x - 3)(x + 1)(x -2)
P(3) = (3 - 3)(3 + 1)(3 -2)
Evaluate
P(3) = 0
Since P(3) = 0, then the linear binomial x - 3 is a factor of P(x) = (x - 3)(x + 1)(x -2)
Read more about the remainder theorem at:
brainly.com/question/13328536
#SPJ1